2011
DOI: 10.1111/j.1744-7976.2010.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Agri-Environmental Regulations, Policies, and Programs

Abstract: The literature on the interface between agriculture and the environment is highly diverse. This paper organizes this literature into three categories: regulation; adoption of environmental best management practices (BMPs) by farmers; and conservation programs. Within each category, the main research questions are set forth. After reviewing select papers, suggestions for future research are discussed. Academic research in this area has been impressive, but many issues and research questions remain unanswered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 68 publications
0
9
0
1
Order By: Relevance
“…Farmers are frequently described as being stewards of the environment and are frequently solicited by society to protect it for the well-being of the current and future generations. Several policies, notably based on a traditional cost-benefit analysis, encourage farmers to participate in conservation programmes and maintain their commitment, but the results fall short of expectations and remain a hot issue in many countries (Vercammen 2011;Lastra-Bravo et al 2015;Liu, Bruins, and Heberling 2018). If activating legacy concerns is effective to enhance attitudes regarding environmental efforts, the aggregated effect can be considerable.…”
Section: Introductionmentioning
confidence: 99%
“…Farmers are frequently described as being stewards of the environment and are frequently solicited by society to protect it for the well-being of the current and future generations. Several policies, notably based on a traditional cost-benefit analysis, encourage farmers to participate in conservation programmes and maintain their commitment, but the results fall short of expectations and remain a hot issue in many countries (Vercammen 2011;Lastra-Bravo et al 2015;Liu, Bruins, and Heberling 2018). If activating legacy concerns is effective to enhance attitudes regarding environmental efforts, the aggregated effect can be considerable.…”
Section: Introductionmentioning
confidence: 99%
“…Another benefit is that time series of these surveys would permit change detection analysis over subsequent 14 years to evaluate climate adaptations, routine monitoring for productivity, soil surveys and yield estimates 15 (Fisette, et al, 2014, Kennedy, et al, 2009; to determine impacts of regulations that may result in the 16 adoption of particular cropping practices in the province (Vercammen, 2011); and to inform recommended 17 methodologies that can be used by industry, provincial or federal organizations for more routine 18 measurement of soil cover. 19 20 This project demonstrated that this method can provide rapid determination and dissemination of post-21 harvest tillage and green cover practices over county level areas even where atmospheric conditions are 22 unfavourable for satellite remote sensing, while improving on financial, temporal, and safety costs for in-23 field verification data acquisition.…”
Section: Conclusion 29mentioning
confidence: 99%
“…This would be an interesting research effort on BMP adoption, but would require holding other factors constant such as producer, farm and commodity characteristics constant as well as program extension efforts, risk, etc. As Vercammen () pointed out in his 2010 Presidential Address, the econometric framework required to examine the intensity of BMP adoption has been overly simplified in most studies, and key modeling issues such as omitted variables, errors in measurement, and endogeneity among important right‐hand side variables should be addressed in examining BMP uptake.…”
Section: Thoughts On Evaluation Of Alberta's Gf Agri‐environmental Prmentioning
confidence: 99%